MEMBERSHIP IN NATIONAL HEALTH INSURANCE AMONG WORKERS IN INDONESIA - Ratna Dwi Wulandari; Agung Dwi Laksono; Tumaji Tumaji; Maria Holly Herawati; Noer Endah Pracoyo; Ina Kusrini (Jurnal Administrasi Kesehatan Indonesia)
Background: The government regulates National Health Insurance (NHI), making it mandatory for everyone. However, at this time, only some, including workers, are NHI members. Moreover, the government regulates who pays these workers' premiums.